2002
DOI: 10.1038/sj.gene.6363834
|View full text |Cite
|
Sign up to set email alerts
|

Atopy in children in relation to BCG vaccination and genetic polymorphisms at SLC11A1 (formerly NRAMP1) and D2S1471

Abstract: The influence of the SLC11A1 (formerly NRAMP1) gene on the association between BCG vaccination and atopy in children was studied in 179 children, BCG vaccinated in infancy, and 307 children without BCG vaccination, all

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
0
24
0
2
Order By: Relevance
“…On a global scale, the (GT) 9 allele has a frequency range of 0.65-0.75 in Afrikaners, 24 African Americans 25 and Caucasians (including the Swedish, 45 Latvians 22 and Columbians 19 ), and of 0.80-0.90 in Africans and Asians (including Chinese, Koreans, 21 Vietnamese, 46 Indians 47 and the Japanese 17,23 ). The (GT) 10 allele (or allele 2) ranks second in frequency (0.10-0.35), while the classical (GT) 11 allele (or allele 1) is usually the least frequent (o0.05).…”
Section: Resultsmentioning
confidence: 99%
“…On a global scale, the (GT) 9 allele has a frequency range of 0.65-0.75 in Afrikaners, 24 African Americans 25 and Caucasians (including the Swedish, 45 Latvians 22 and Columbians 19 ), and of 0.80-0.90 in Africans and Asians (including Chinese, Koreans, 21 Vietnamese, 46 Indians 47 and the Japanese 17,23 ). The (GT) 10 allele (or allele 2) ranks second in frequency (0.10-0.35), while the classical (GT) 11 allele (or allele 1) is usually the least frequent (o0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps polymorphisms in the human NRAMP1 gene, and other infection-related genes, could contribute to the inverse correlation between bacterial infection and allergic diseases. Polymorphisms in the genomic region of human NRAMP1 are associated with the risk of atopy in BCG-vaccinated children [23]. Moreover, the Nramp1 gene is involved in several other diseases of deregulated immunity: a polymorphism in the promoter region of NRAMP1 has been associated with inflammatory bowel disease [24], rheumatoid arthritis [25], multiple sclerosis [26] and type 1 diabetes mellitus [27].…”
Section: Infectious Agents and The Hygiene Hypothesismentioning
confidence: 99%
“…Other investigators already suggested that polymorphisms in the genomic region of NRAMP1 are associated with risk of atopy in BCG-vaccinated children (20). The current controversy about the efficacy of mycobacteria and their components in the treatment of allergic asthma in humans (46,47) can be explained by the strong influence of genetic factors, such as the NRAMP1 gene, on the inverse relationship between infection and the development of allergic disease.…”
Section: Cd25mentioning
confidence: 99%
“…In humans, association or linkage of NRAMP1 with susceptibility to infectious diseases, but also atopy and autoimmune disease, has been demonstrated (20,21). The murine polymorphism of Nramp1 is apparent as either low (Nramp1 s ) or high (Nramp1 r ) resistance of macrophages to the growth of intracellular organisms.…”
mentioning
confidence: 99%